Synthesis of Styrene-Acrylate Copolymers by RAFT, Useable like Modifications of Coatings - Boháčik, Peter; Podzimek, Štěpán; Špaček, V. (CHEMagazín, s.r.o., 2016)
The copolymers are prepared by Reversible addition-fragmentation Chain Transfer Polymerization (RAFT) and are characterized by size exclusion chromatography (SEC). Coating films were cast on steel panels and were evaluated by standard coatings tests.
Syntéza styren-akrylátových kopolymerů jako modifikátory vlastností nátěrových hmot metodou RAFT
Keywords: RAFT; styrene-acrylate copolymers; modification of coatings; RAFT; styren-akrylatove kopolymery; modifikace natěrtových hmot